Creative strategies to support student learning through reflection - van Rensburg, G.H.; Botma, Y.; Heyns, T.; Coetzee, I.M. (South African Journal of Higher Education, 2018)
Reflective practice has become a key attribute of promoting quality teaching and learning. Learning is an active process and include reflective writing, visualising and verbalising to promote critical thinking. In our experience most often than not superficial reflective writing is used. We explored the design of opportunities for students to engage in critical reflection. Theoretical data were obtained through in-depth exploration of the literature to allow contextualisation while arguing a case. A qualitative approach was used. Judgements were not made about the measured quality of reported findings, but on the relevance of reflective strategies to support students, enhance critical reflection and transform practice. Combined with narration and dialogue, reflection can bridge the gap between theoretical ideals and realities of the practice context. Four reflective activities have been identified that could be used to engage students in critical reflection.